1996
DOI: 10.1126/science.271.5255.1597
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Degradation of the G 1 Cyclin Cln2 Induced by CDK-Dependent Phosphorylation

Abstract: Cyclins regulate the major cell cycle transitions in eukaryotes through association with cyclin-dependent protein kinases (CDKs). In yeast, G1 cyclins are essential, rate-limiting activators of cell cycle initiation. G1-specific accumulation of one G1 cyclin, Cln2, results from periodic gene expression coupled with rapid protein turnover. Site-directed mutagenesis of CLN2 revealed that its phosphorylation provides a signal that promotes rapid degradation. Cln2 phosphorylation is dependent on the Cdc28 protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
201
1
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(209 citation statements)
references
References 25 publications
5
201
1
2
Order By: Relevance
“…If degradation of p27 has similarities to the degradation of G1 cyclins in S. cerevisiae, our observations may be equivalent to the recognition of phosphorylated Cln2 by a Cdc53/Cdc34/Cdc4 complex which precedes its degradation (e.g. Bai et al, 1996;Lanker et al, 1996;Willems et al, 1996). In this sense, the Myc-dependent sequestration' of p27 reported by Amati and colleagues may refer to the formation of a similar complex (Vlach et al, 1996).…”
Section: Discussionsupporting
confidence: 55%
“…If degradation of p27 has similarities to the degradation of G1 cyclins in S. cerevisiae, our observations may be equivalent to the recognition of phosphorylated Cln2 by a Cdc53/Cdc34/Cdc4 complex which precedes its degradation (e.g. Bai et al, 1996;Lanker et al, 1996;Willems et al, 1996). In this sense, the Myc-dependent sequestration' of p27 reported by Amati and colleagues may refer to the formation of a similar complex (Vlach et al, 1996).…”
Section: Discussionsupporting
confidence: 55%
“…BLM contains an L2G box (amino-acids 406 ± 432) which could serve as an E6-AP speci®c substrate recognition site for ubiquitination, as described for the Mcm7 protein (KuÈ hne and Banks, 1998). Furthermore, uctuations of BLM levels during the cell cycle were evocative of a protein degraded through the ubiquitin- proteasome pathway, similar to geminin, an inhibitor of DNA replication (McGarry and Kirschner, 1998), and several cases of phosphorylation promoting ubiquitination have been described (i.e., see Clurman et al, 1996;Lanker et al, 1996). We thus asked the question whether BLM could be targeted for degradation through a ubiquitin conjugation process.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years it has become clear that phosphorylation plays an important regulatory role in the degradation of a number of proteins (for example see, Nishizawa et al, 1992;Chen et al, 1995;Lanker et al, 1996;Skowyra et al, 1997). p53 is a well known phosphoprotein which contains a number of phosphorylation sites in the N-terminal as well as in the Cterminal region (Steegenga et al, 1996;Meek et al, 1997), and it has been reported that mutation of the known phosphorylation sites at positions 15 and 315 a ects the p53 turnover rate (Fiscella et al, 1993;Lin and Desiderio, 1993).…”
Section: Introductionmentioning
confidence: 99%